Investigating the practice of assessment in augmenting creativity: A postgraduate perspective / Jacqueline Susan Anak Rijeng - Rijeng, Jacqueline Susan (2011)
The advent of creativity in the Malaysian institutes of higher education has brought significant changes to the role of assessment in higher education today. The impetus leads to major transformations especially in implementing suitable assessment approaches in the curriculum. With this in mind, a study was conducted to explore postgraduate students’ perceptions of assessment and its influence on students’ creativity. The conceptual framework for the present study was built based on the integration of convergent and divergent thinking (Guilford, 1950) as well as the Bloom’s taxonomy (1956) that underpins the assessment approaches towards cultivating creativity. A mixed method research design was used to carry out the research which includes questionnaire surveys, interviews and document analysis. Participants involved a group of final year full-time postgraduate students (n=40) from three different programmes in the Faculty of Education, Universiti Teknologi MARA (UiTM), Shah Alam. Findings revealed that students generally have a positive attitude towards assessment as an integral aspect in the classroom. Students’ perception was indicated the highest when it comes to the transparency of assessment (M = 4.114, SD = 0.648). However, students reported that they lack the flexibility when dealing with the preferred assessment. Interestingly, oral presentation is perceived to be one of the best assessment methods that could enhance creative ability, suggesting various ways that presentations could be carried out creatively. Finally, the analysis of documents involving the course information and grading matrix also confirmed the emphasis given to creativity in the existing curriculum. The implications of the study include the need for curriculum development which takes into account some of the best practices across different programmes to be implemented in postgraduate education as well as giving more emphasis on self-assessment and alternative assessment. Also, curriculum negotiation is another important practice that should be considered by the faculty. It is therefore recommended that existing courses be re-evaluated by including more variation to assessment tasks as well as showing appreciation for creative expression given by students. This study could benefit instructional leaders, adult learners and policy makers in deciding the potentials of classroom assessment towards developing creativity in higher education.